The effects of violent video game habits on adolescent hostility, aggressive behaviors, and school performance - Gentile, Douglas A.; Lynch, Paul J.; Linder, Jennifer Ruh; Walsh,David A. (Academic Press, 2004)
Video games have become one of the favourite activities of American children. A growing body of research is linking violent video game play to aggressive cognitions, attitudes, and behaviours. The first goal of this study was to document the video games habits of adolescents and the level of parental monitoring of adolescent video game use. The second goal was to examine associations among violent video game exposure, hostility, arguments with teachers, school grades, and physical fights. In addition, path analyses were conducted to test mediational pathways from video game habits to outcomes. Six hundred and seven 8th- and 9th-grade students from four schools participated. Adolescents who expose themselves to greater amounts of video game violence were more hostile, reported getting into arguments with teachers more frequently, were more likely to be involved in physical fights, and performed more poorly in school. Mediational pathways were found such that hostility mediated the relationship between violent video game exposure and outcomes. Results are interpreted within and support the framework of the General Aggression Model.